Comparison of different methods of ABI acquisition for detection of peripheral artery disease in diabetic patients - Homza, Miroslav; Machaczka, Ondrej; Porzer, Martin; Kozak, Milan; Plasek, Jiri; Sipula, David (Biomedical papers, 2019)
Background: Ankle brachial index (ABI) is the principal screening method for peripheral arterial disease (PAD). In this study, we compare various types of Doppler-derived and oscillometric ABIs with results obtained through duplex ultrasonography. Methods: 62 patients were enrolled in the study. For each limb, blood pressures for both ankle arteries and the arm were measured using Doppler and an automated oscillometric device. Duplex ultrasound was performed for all limbs and occlusions >50% were considered PAD-positive. ABI was calculated using both higher (HABP) and lower (LABP) arterial blood pressure on the individual limbs and the ability to predict duplex-detected stenoses was evaluated. Results: LABP calculation provided results superior to the guideline-recommended HABP. Considering patients with ABI >1.4 or measurement failure as PAD-positive further enhanced the test parameters. The higher ABI cut-off of 1.0 resulted in somewhat better sensitivities (max 92%) and negative predictive values (max 87%) at the expense of a substantial increase in the number of false positives. Oscillometric method yielded poor sensitivities but very good specificities (max 94%) and positive predictive values (max 90%). Conclusions: Doppler-based LABP provides better results than the guideline-recommended HABP in diabetic patients, nevertheless even this method is not perfect. Increasing the cut-off value to 1.0 in these patients does not bring a substantial improvement of the test performance. Patients with high ABI should be automatically considered PAD-positive and referred for further investigation using imaging techniques.
Keywords: ankle brachial index; diabetes; oscillometric measurement; dopplerometric measurement; duplex ultrasonography